Lateral and Normal Diffusion in Popc/Sopc/Sape/Pope Mixed Bilayer: A Molecular Dynamics Study - Gharabekyan, Hrant; Poghosyan, Armen (ՀՀ ԳԱԱ)
We have performed a 40-ns molecular dynamics simulation of POPC/SOPC/SAPE/POPE mixed Bilayer. The diffusion properties of lipid molecules have been studied. The corresponding diffusion coefficients of lipids have been estimated, and the findings are in good agreements with experimental data. Մենք իրականացրել ենք POPC / SOPC / SAPE / POPE խառը լիպիդային համակարգի մոդելավորում մոլեկուլային դինամիկայի մեթոդով (40 նվ): Ուսումնասիրվել են լիպիդային մոլեկուլների դիֆուզիոն հատկությունները: Գնահատվել են համապատասխան դիֆուզիոն գործակիցները, և ստացվել է բավականին լավ համընկում փորձարարական տվյալների հետ: Мы провели 40-нс моделирование молекулярной динамики смешанного бислоя POPC/SOPC/SAPE/POPE. Изучены диффузионные свойства липидных молекул. Соответствующие коэффициенты диффузии липидов были оценены, и результаты находятся в хорошем согласии с экспериментальными данными.
Keywords: Biology